2006
DOI: 10.1126/science.1118642
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Plant Responses to Environmentally Activated Phytohormonal Signals

Abstract: Plants live in fixed locations and survive adversity by integrating growth responses to diverse environmental signals. Here, we show that the nuclear-localized growth-repressing DELLA proteins of Arabidopsis integrate responses to independent hormonal and environmental signals of adverse conditions. The growth restraint conferred by DELLA proteins is beneficial and promotes survival. We propose that DELLAs permit flexible and appropriate modulation of plant growth in response to changes in natural environments. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
1,082
2
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,336 publications
(1,172 citation statements)
references
References 25 publications
42
1,082
2
7
Order By: Relevance
“…The importance of this family has been made clear through a number of functional studies (Di Laurenzio et al, 1996;Peng et al, 1997;Silverstone et al, 1998), and a remarkable number of GRAS proteins have been identified in more than 294 embryophyta species (Finn et al, 2010;Sun et al, 2012). Most of these proteins play key roles in the transcriptional regulation and signaling transduction related to plant growth and development (Bolle, 2004;Achard et al, 2006). Examples include Arabidopsis thaliana DELLA in gibberellin (GA) signaling during regulation of plant growth (Peng et al, 1997;Sun and Gubler, 2004;Murase et al, 2008), Medicago truncatula NSP1-NSP2 in DNA promoter regulation for nodulation signaling (Kaló et al, 2005;Smit et al, 2005;, Arabidopsis SCR-SHR in regulation of radial patterning for root and shoot (Pysh et al, 1999;Helariutta et al, 2000;Nakajima et al, 2001), Lilium longiflorum SCL in auxin and stress-induced signaling (Morohashi et al, 2003;Sánchez et al, 2007), At-PAT1 in phytochrome light signal transduction and plant defense (Bolle et al, 2000;TorresGalea et al, 2006), At-LAS in axillary meristem development (Schumacher et al, 1999;Greb et al, 2003), and Petunia hybrida HAM in shoot meristem maintenance (Stuurman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this family has been made clear through a number of functional studies (Di Laurenzio et al, 1996;Peng et al, 1997;Silverstone et al, 1998), and a remarkable number of GRAS proteins have been identified in more than 294 embryophyta species (Finn et al, 2010;Sun et al, 2012). Most of these proteins play key roles in the transcriptional regulation and signaling transduction related to plant growth and development (Bolle, 2004;Achard et al, 2006). Examples include Arabidopsis thaliana DELLA in gibberellin (GA) signaling during regulation of plant growth (Peng et al, 1997;Sun and Gubler, 2004;Murase et al, 2008), Medicago truncatula NSP1-NSP2 in DNA promoter regulation for nodulation signaling (Kaló et al, 2005;Smit et al, 2005;, Arabidopsis SCR-SHR in regulation of radial patterning for root and shoot (Pysh et al, 1999;Helariutta et al, 2000;Nakajima et al, 2001), Lilium longiflorum SCL in auxin and stress-induced signaling (Morohashi et al, 2003;Sánchez et al, 2007), At-PAT1 in phytochrome light signal transduction and plant defense (Bolle et al, 2000;TorresGalea et al, 2006), At-LAS in axillary meristem development (Schumacher et al, 1999;Greb et al, 2003), and Petunia hybrida HAM in shoot meristem maintenance (Stuurman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This observation is in contrast to the previous finding that high salinity imposes osmotic stress in inhibiting seed germination. 18,19 One possible scenario is that the NTL8-mediated pathway is a specific salt signaling pathway that exerts its role only under high salinity, while the ABA-mediated salt signaling pathway plays a somewhat general role in seed germination under a variety of environmental stress conditions.…”
mentioning
confidence: 99%
“…Ethylene has an important role in many aspects of plant biology, from seed germination to dormancy, ripening and senescence, and the regulation of stomatal closure (by promoting NADPH oxidase-mediated reactive oxygen species (ROS) production in stomatal guard cells) as well as defences against biotic and abiotic stresses (Bartoli et al, 2013). According to Achard et al (2006), ethylene signalling pathways might be essential for survival under adverse environmental conditions and it is involved in control of growth as well as stress tolerance. For example, drought induced the accumulation of the ethylene precursor and the activation of ethylene signalling leading to a reversible arrest of cell cycle (Bartoli et al, 2013).…”
Section: Articlementioning
confidence: 99%